Social-family network and self-employment: Evidence from temporary rural-urban migrants in China - Junfu Zhang; Zhong Zhao (Institute for the Study of Labor (IZA), 2011)
We hypothesize that individuals with a larger social-family network are more likely to choose self-employment. We test this hypothesis using data on temporary rural-urban migrants in China. The size of a migrant's social-family network is measured by the number of relatives and friends this migrant greeted during the past Spring Festival. Our empirical analysis faces two challenges. First, there is an endogeneity problem in that a migrant may want to develop and maintain a large social-family network exactly because he is self-employed. For this reason, a simple correlation between the probability of being self-employed and the size of the migrant's social-family network cannot be interpreted as causal. Second, the size of the social-family network is measured using survey data, which is subject to measurement error. To overcome these problems, we take an instrumental variable (IV) approach. More specifically, we examine the distance an individual migrated when he first moved to a city and use this variable to instrument for the current size of the social-family network. We establish the credibility of the IV by emphasizing the unique institutional context of rural-urban migration in China and focusing on the sample of migrants who originally started as wage workers in urban areas and currently are not in their first jobs. Our IV results indeed show that a rural-urban migrant with a larger social-family network is more likely to be self-employed in the city. This finding is robust to alternative model specifications and various restrictions on the sample used in estimation.
urn:nbn:de:101:1-201104113195
Keywords: J23; J61; D85; 330; social-family network; self-employment; rural-urban migrants; Selbstständige; Familie; Soziales Netzwerk; Landflucht; Schätzung; China